2012
DOI: 10.1590/s0034-89102012005000036
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de intervenções sobre o índice de massa corporal em escolares

Abstract: OBJECTIVE:To evaluate the effect of intervention programs using nutritional education, physical activity or both on the reduction of body mass index in school-age students. METHODS:The systematic review with meta-analysis included randomized controlled studies available from the following electronic databases for the years 1998 to 2010: PubMed, Lilacs, Embase, Scopus, Web of Science and Cochrane Library. The descriptors were: randomized controlled trial, overweight, obesity, body mass index, child, adolescent,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
31

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 49 publications
0
26
0
31
Order By: Relevance
“…A systematic literature review identified a reduction of body mass index after participation in physical activity by first grade school students. 27 Similarly, the knowledge about how to prepare food improved after educational intervention proposed in the study, mainly because in the second stage of the investigation children believed boiling is the healthier way to prepare food. This is a relevant result because food preparation involves issues related to culture, which is difficult to manage, as highlighted in a study about nutritional problems.…”
Section: Discussionmentioning
confidence: 84%
“…A systematic literature review identified a reduction of body mass index after participation in physical activity by first grade school students. 27 Similarly, the knowledge about how to prepare food improved after educational intervention proposed in the study, mainly because in the second stage of the investigation children believed boiling is the healthier way to prepare food. This is a relevant result because food preparation involves issues related to culture, which is difficult to manage, as highlighted in a study about nutritional problems.…”
Section: Discussionmentioning
confidence: 84%
“…Isso evidencia a discrepância entre a abordagem meramente educativa do ponto de vista nutricional e a abordagem associada à atividade física. Atividades de EAN isoladamente não produzem efeitos positivos significativos na redução do IMC ou composição corporal entre escolares, somente quando associados à prática de atividade física 24 .…”
Section: Discussionunclassified
“…A previsão para os próximos anos é de que haja crescimento das indústrias de banda larga e vídeo em tela, com ênfase nos consumidores mais jovens, o que contribuirá para o estilo de vida não saudável. 21 Somada a esse cenário preocupante existe a influência dos hábitos dos pais, conforme mencionaram as enfermeiras. É fundamental para a enfermagem planejar a intervenção na base familiar, uma vez que programas de intervenções apresentam melhores resultados quando as estratégias utilizadas incluem o componente familiar.…”
Section: Está Relacionado Ao Estilo De Vida Porque Tem Muito Fast Founclassified
“…É fundamental para a enfermagem planejar a intervenção na base familiar, uma vez que programas de intervenções apresentam melhores resultados quando as estratégias utilizadas incluem o componente familiar. 21,22 De modo geral, as participantes do presente estudo identificaram a causa da obesidade como multifatorial. O planejamento, então, deve partir de uma esfera mais abrangente, no qual a prioridade são políticas públicas de encorajamento de hábitos saudáveis para toda a população.…”
Section: Está Relacionado Ao Estilo De Vida Porque Tem Muito Fast Founclassified
See 1 more Smart Citation